Surveillance of adamantane resistance among influenza A H3 viruses isolated in Argentina between 2001 and 2007 - Pontoriero, Andrea (2008)
Fil: Pontoriero, A. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Virosis Respiratoria; Argentina.